2010
DOI: 10.1039/b911725c
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of reduction of maleate and fumarate by NiI(1,4,8,11-tetraazacyclotetradecane)+ in aqueous solutions

Abstract: Ni(I)(1,4,8,11-tetraazacyclotetradecane)(+), Ni(I)L(+), was produced in neutral aqueous solutions by radiolytic techniques. The mechanism and kinetics of the reaction of Ni(I)L(+) with maleate and fumarate were studied applying pulse-radiolysis and analysis of the final products. Surprisingly the mechanisms of reduction of maleate and fumarate differ considerably. Based on the results it was also shown that Ni(II)L(2+) is an electrocatalyst for the reduction of alkenes in aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The mechanism observed in the CoL-maleate systems is similar to that observed in the NiL 2 system [34] in that initially maleate forms a -complex with the central metal cation. It differs from that observed for the NiL 2 system in that the yield of succinate is y = 1270x -3000 considerably lower in the cobalt system.…”
Section: ð15þsupporting
confidence: 57%
See 1 more Smart Citation
“…The mechanism observed in the CoL-maleate systems is similar to that observed in the NiL 2 system [34] in that initially maleate forms a -complex with the central metal cation. It differs from that observed for the NiL 2 system in that the yield of succinate is y = 1270x -3000 considerably lower in the cobalt system.…”
Section: ð15þsupporting
confidence: 57%
“…CO À 2 , on the mechanism of reduction of alkenes by Ni(I)L þ yielded the following results [34]. The mechanisms of reduction of maleate and fumarate by [Ni(I)L 1 ] þ differ significantly from each other in spite of the similarity of the two substrates.…”
Section: Introductionmentioning
confidence: 93%
“…Future studies will use recently reported methods to determine the mechanism of proton reduction on iron porphyrins and exploit our ability to modulate the effective rate of proton transfer to the catalyst’s active site. For instance, in cases where H 2 evolution represents a parasitic side reaction, such as carbon dioxide reduction, , nitrite reduction, and olefin reduction in the acidic solutions, we wish to tailor the rate of proton transfer to the catalyst active site in order to minimize parasitic evolution of H 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar reactivity under reductive conditions was also reported for other alkenes earlier always accompanied by dimerization. [287][288][289][290] In combination with molecular nickel phosphine hydrogenation catalysts, 4 mediates the hydrogenation of alkynes and enones. 291 The application of the simple complex Ni(bpy) 3 2+ 5 (bpy = 2,2 0 -bipyridine) enabled the semihydrogenation of alkynes via molecular electrosynthesis.…”
Section: Overviewmentioning
confidence: 99%
“…Similar reactivity under reductive conditions was also reported for other alkenes earlier always accompanied by dimerization. 287–290 In combination with molecular nickel phosphine hydrogenation catalysts, 4 mediates the hydrogenation of alkynes and enones. 291…”
Section: Catalystsmentioning
confidence: 99%